Incidental Low‐Grade Gliomas: Single‐Institution Management Based on Clinical, Surgical, and Molecular Data. Issue 3 (March 2020) - Ius, Tamara; Cesselli, Daniela; Isola, Miriam; Pauletto, Giada; Tomasino, Barbara; D'Auria, Stanislao; Bagatto, Daniele; Pegolo, Enrico; Beltrami, Antonio Paolo; di Loreto, Carla; Skrap, Miran
Abstract : BACKGROUND: : Incidentally discovered diffuse low‐grade gliomas (iLGG) are poorly documented in the literature. They are diagnosed by chance during radiological examinations. OBJECTIVE: : To review a cohort of patients with iLGG surgically treated in our institution, analyzing clinical, molecular, and surgical aspects. METHODS: : Clinical, radiological, and treatment data of iLGG were retrieved and compared with those of symptomatic diffuse LGGs (sLGG). Histological and molecular review was carried out as well. The extent of resection was evaluated on preoperative and postoperative T2‐weighted magnetic resonance imaging. RESULTS: : Thirty‐four iLGG cases were identified within a monoinstitutional cohort of 332 patients operated for low‐grade gliomas from 2000 to 2017. Clinically, patients with iLGG had higher preoperative karnofsky performance scale (KPS) ( P = .003), smaller tumor volume ( P = .0001), lower frequency of eloquent areas involvement ( P = .0001), and higher rate of complete resection ( P = .0001) compared to those with sLGG. No differences in the molecular profile and O 6 ‐methylguanine‐DNA‐methyltransferase promoter methylation were detected between iLGG and sLGG. Importantly, patients with iLGG had longer overall survival than those with sLGG ( P = .0001), even when a complete surgical resection was achieved ( P = .001). CONCLUSION: : Although the therapeutic strategy of iLGG is still a matter of debate, our data support the safety and the effectiveness of early surgical resection. The favorable prognosis of iLGG may be due to the higher practicability of extensive resection, noneloquent tumor location, and smaller tumor volume.